DEVELOPMENT OF GLYCEROL BASED MICROFLUIDIC FUEL CELL - Panjaira, Deoashish (IIT(BHU), Varanasi, 2021)
In the present world scenario, limited resources of fossil fuels with high demand are the major cause for researchers to develop environment friendly power generating devices. The fuel cell device produces energy without any toxic emissions to the environment. Microfluidic fuel cells (MFCs) are one of the most recently developed and investigated micro fuel cell device which has created interest among the researchers these days for further studies due to its possible potential uses in portable electrical and electronic devices. In MFC, the electrodes are fixed in a microchannel with a distance between electrodes of less than 1 mm without having any solid membrane electrolyte
This Thesis submitted by IIT(BHU), Varanasi PHd Scholar & supervised by Hiralal Pramanik)
Keywords: GLYCEROL; MICROFLUIDIC